Integrative delineation of species of Mediterranean freshwater planarians (Platyhelminthes: Tricladida: Dugesiidae). (29th October 2013) - Sluys, Ronald; Solà, Eduard; Gritzalis, Konstantinos; Vila‐Farré, Miquel; Mateos, Eduardo; Riutort, Marta
Abstract : The paper presents an integrative taxonomic study on dugesiid freshwater flatworms from the north‐eastern Mediterranean region by applying both morphological and molecular criteria in the formulation of stable species hypotheses. The morphological information obtained for the specimens was used in a traditional way by comparing the organismal traits of the various populations and candidate species with those of known species, as documented in the taxonomic literature and as revealed by examination of histological sections of museum specimens. In the molecular species delimitation the General Mixed Yule‐Coalescent method (GMYC) was used. Results of this study (1) supported the presence of 13 Dugesia species in the Hellenic area (including D. sicula  Lepori, 1948, a pan‐Mediterranean species), (2) culminated in the description of four new Dugesia species, (3) suggested the presence of two Confirmed Candidate Species, (4) pointed to 12 GMYC‐delimited units in Greece and two in Slovakia as Unconfirmed Candidate Species and (5) revealed the presence of an entirely new genus, represented by two newly described species and a third Unconfirmed Candidate Species. Our results revealed a high diversity of dugesiid species in this relatively small region. It is concluded that the morphological features used by taxonomists in comparative studies of dugesiid flatworms generally result in reliable identifications and delineations of species taxa, except in the case of cryptic species. © 2013 The Linnean Society of London